Gold leaching in cyanide-starved copper solutions in the presence of glycine - Oraby, E.; Eksteen, Jacques (Elsevier, 2015)
© 2015 Elsevier B.V. Abstract In the cyanidation of copper-gold ores, the presence of copper minerals can lead to soluble gold losses, the production of weak acid dissociable (WAD) cyanide, as well as a number of operational challenges in CIP/CIL circuits with regard to competitive adsorption, and subsequent difficulties associated with elution, electrowinning and smelting. In addition, copper minerals are significant cyanide consumers, leading to higher cost in ore treatment. This paper presents a process to enhance the dissolution of gold using copper-cyanide solutions in the presence of glycine where the solution is cyanide starved. The effect of glycine addition on gold leaching kinetics in copper-cyanide solutions under different leaching conditions was studied. The results show that, in the presence of glycine, gold dissolution rate increases significantly in solutions containing copper-cyanide species at a very low, or zero, free cyanide concentration. In the presence and absence of glycine, gold dissolution rates in solutions containing 10 mM Cu(CN)32 - were 11.1 µmol/m2·s and 0.65 µmol/m2·s, respectively. It is shown that the average gold dissolution rate in a Cu-CN--glycine system is about 6.5 times higher than the gold dissolution rate in the conventional cyanidation, the presence of cyanide being similar in each system. Kinetic and electrochemical studies were conducted to evaluate the effects of glycine concentration, pH, CN/Cu ratio, and initial copper concentrations on the dissolution of gold. It has also been shown that the gold dissolution rate increases by increasing the glycine concentration up to 1 g/L and any further glycine addition has a negative effect on the dissolution of gold. Increasing leaching pH up to 12 enhances gold dissolution in the copper-cyanide-glycine solutions. However, increasing leaching pH to 13 has an adverse effect on the dissolution of gold.